Hubungan Peran Kader Terhadap Kehadiran Lansia Dalam Mengikuti Posyandu Lansia Di Wilayah Kerja Puskesmas Simpang Bahjambi Nagori Senio Kabupaten Simalungun Tahun 2025 - Nur Masdalifah; Sondang Sidabutar; Tegar Sasongko; Tasya Fadilah (Politeknik Ganesha Medan, 2025)
This study aims to determine the relationship between the role of cadres and the attendance of elderly people in attending the Elderly Integrated Health Post (Posyandu Lansia) in the Simpang Bahjambi Community Health Center (Puskesmas), Senio Village, Simalungun Regency in 2025. The study design used was cross-sectional. The study population included all elderly people aged 60–70 years who resided in the Simpang Bahjambi Community Health Center (Puskesmas), Senio Village. The study sample consisted of 70 respondents obtained through total sampling technique. Data collection was carried out using a questionnaire, while data analysis was applied using the Spearman's Rho test (α = <0.1), resulting in a p-value of 0.000. This indicates a significant relationship between the role of cadres and the active participation of elderly people in Posyandu Lansia (Lansia Integrated Health Post) in the Simpang Bahjambi Community Health Center (Puskesmas), Senio Village, Simalungun Regency, in 2025. The results of this study are expected to provide information on the importance of the role of cadres in implementing Posyandu Lansia activities. As a recommendation, Posyandu Lansia cadres are encouraged to provide facilities and infrastructure more regularly, provide information regarding the direction and schedule of upcoming Posyandu Lansia activities, and increase the frequency of monitoring elderly people during activities.